Did I find the right examples for you? yes no

# numpy.polynomial.hermite.hermdiv

All Samples(2)  |  Call(2)  |  Derive(0)  |  Import(0)
```Divide one Hermite series by another.

Returns the quotient-with-remainder of two Hermite series
`c1` / `c2`.  The arguments are sequences of coefficients from lowest
order "term" to highest, e.g., [1,2,3] represents the series
``P_0 + 2*P_1 + 3*P_2``.

Parameters
----------
c1, c2 : array_like(more...)
```

```        def hermdiv(c1, c2):
"""
Divide one Hermite series by another.

Returns the quotient-with-remainder of two Hermite series
`c1` / `c2`.  The arguments are sequences of coefficients from lowest
order "term" to highest, e.g., [1,2,3] represents the series
``P_0 + 2*P_1 + 3*P_2``.

Parameters
----------
c1, c2 : array_like
1-D arrays of Hermite series coefficients ordered from low to
high.

Returns
-------
[quo, rem] : ndarrays
Of Hermite series coefficients representing the quotient and
remainder.

--------

Notes
-----
In general, the (polynomial) division of one Hermite series by another
results in quotient and remainder terms that are not in the Hermite
polynomial basis set.  Thus, to express these results as a Hermite
series, it is necessary to "reproject" the results onto the Hermite
basis set, which may produce "unintuitive" (but correct) results; see
Examples section below.

Examples
--------
>>> from numpy.polynomial.hermite import hermdiv
>>> hermdiv([ 52.,  29.,  52.,   7.,   6.], [0, 1, 2])
(array([ 1.,  2.,  3.]), array([ 0.]))
>>> hermdiv([ 54.,  31.,  52.,   7.,   6.], [0, 1, 2])
(array([ 1.,  2.,  3.]), array([ 2.,  2.]))
>>> hermdiv([ 53.,  30.,  52.,   7.,   6.], [0, 1, 2])
(array([ 1.,  2.,  3.]), array([ 1.,  1.]))

"""
# c1, c2 are trimmed copies
[c1, c2] = pu.as_series([c1, c2])
if c2[-1] == 0 :
raise ZeroDivisionError()

lc1 = len(c1)
lc2 = len(c2)
if lc1 < lc2 :
return c1[:1]*0, c1
elif lc2 == 1 :
return c1/c2[-1], c1[:1]*0
else :
quo = np.empty(lc1 - lc2 + 1, dtype=c1.dtype)
rem = c1
for i in range(lc1 - lc2, - 1, -1):
p = hermmul([0]*i + [1], c2)
q = rem[-1]/p[-1]
rem = rem[:-1] - q*p[:-1]
quo[i] = q
return quo, pu.trimseq(rem)
```

```                cj = [0]*j + [1]
quo, rem = herm.hermdiv(tgt, ci)
```                cj = [0]*j + [1]